The Intellectual Bases in the Ismaeli Ideology from Al-Jabiri’s Perspective - Shoufyeen, Eyad (Jordan Journal of Social Sciences, 2020)
The Moroccan thinker, Muhammad Aabed al-Jabiri, considered the intellectual bases on which the Ismaeli ideology had stood in building up its ideology can be abbreviated in three: the Letters of Ikhwan al-Safa, the philosophy of Ibn Sina and the ideology of the Fatimid State. The relationship of Ismaelism with the said references looks quite vague and needs deep research to prove this relationship, because there are no direct indications in the Letters that confirm its Ismaili origin. Besides, Ibn Sina had never publicly declared his Ismaili ideology. The Fatimid State, had adopted the Ismaeli ideology most of the time, while in certain times, it was more in favor of the Ithnay-Ashriyya ideology. This study is concerned with clarifying the relationship between the Isamili ideology and the three afore-mentioned references. Al-Jabiri believes that the letters have clear-cut Hurmusi roots that had clear influence upon Isamilism. Ibn-Sina’s philosophy does have certain’irfani roots inherited from al-Farabi as well as from the emanation philosophy of Plotinus .